Pengaruh Feed Rate dan Sudut Kemiringan Tool Micro Friction Stir Welding Sambungan Aluminium 1100 - Rahman, Muhammad Budi Nur; Nugroho, Aris Widyo; Putra, Ramadhoni Fahmi Arianto; Arfiansyah, Nur Indra (Universitas Muhammadiyah Yogyakarta, 2023)
Micro friction stir welding (µFSW) is friction stir welding for a maximum thickness of 1 mm. The aim of the research was to determine the effect of the feed rate and the tilt angle of the pin tool on 1100 µFSW aluminum. Welding was carried out with variations in the angle of the tool tilt of 0°, 1° and 2°, with variations in the feed rate of 66, 85, and 120 mm/min and the pin rotation speed. tools 2280rpm. The type of connection used is the butt joint. The tests carried out were testing the microstructure and macro defects with an optical microscope, hardness test, and tensile strength test. The results of the macro test showed that there were defects in the feed rate variations, namely incomplete fusion defects. The results of microstructure testing showed that the grain size of the stir zone (SZ) of all variations was smaller than that of BM and HAZ causing the hardness values of HAZ and SZ to be higher than that of BM. As the speed of the feed rate and the angle of inclination of the tool increase, the hardness of the SZ region and the tensile strength increase. High heat input results in slower cooling resulting in larger grains and causes a decrease in hardness values. The highest hardness at a feed rate of 120 mm/minute is 73.7 VHN and the slope of the tool 2o is 64.7 VHN. The highest strength at a feed rate of 120 mm/min is 84.84 MPa and at an angle of 2o is 111.36 MPa.